Decline of Child Sexual Abuse in US: What can be learned? - Finkelhor, David (Zeitschrift für Psychotraumatologie und psychologische Medizin, 2006)
The impact of sexual victimization of children can be devastating on the health and wellbeing of the victims. This article examined definition, prevalence any types of sexual abuse of children as well as possible explanations for the decline, particularly in the U.S. in Child Sexual Abuse Cases. The author underlines the distinctions among the cases, particularly between victims and offenders and that the policies and interventions need to consider the diversity of the problem. Child sexual abuse has many forms and accordantly different impact in the victims and different motivations on the side of the offenders.